The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2024
DOI: 10.1039/d4dd00057a
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput quantum theory of atoms in molecules (QTAIM) for geometric deep learning of molecular and reaction properties

Santiago Vargas,
Winston Gee,
Anastassia Alexandrova

Abstract: We present a package, Generator, for geometric molecular property prediction based on topological features of quantum mechanical electron density. Generator computes Quantum Theory of Atoms in Molecules (QTAIM) features, at...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 63 publications
0
0
0
Order By: Relevance
“…Despite these advances for molecular property prediction, the prediction of computed reaction properties (principally, reaction barriers ,, ) is still in its infancy . Machine learning approaches span from utilizing simple two-dimensional fingerprints of reaction components , (reactants and products) to physical-organic descriptors, ,,,, or electronic structure-inspired features, to transformer models , adapted for regression, and 2D graph-based approaches. ,,, The latter, particularly the ChemProp model, , are often best-in-class in predicting reaction properties . It has been shown that these models achieve their impressive performance by exploiting atom-mapping information, which provide information analogous to the reaction mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these advances for molecular property prediction, the prediction of computed reaction properties (principally, reaction barriers ,, ) is still in its infancy . Machine learning approaches span from utilizing simple two-dimensional fingerprints of reaction components , (reactants and products) to physical-organic descriptors, ,,,, or electronic structure-inspired features, to transformer models , adapted for regression, and 2D graph-based approaches. ,,, The latter, particularly the ChemProp model, , are often best-in-class in predicting reaction properties . It has been shown that these models achieve their impressive performance by exploiting atom-mapping information, which provide information analogous to the reaction mechanism.…”
Section: Introductionmentioning
confidence: 99%